Thermophysical properties of N-phenyl-N-ethanol ammonium carboxylate based ionic liquids: Measurements, correlations and COSMO-RS study - Chennuri, B.K. (Elsevier B.V., 2017)
In this work, a series of four protic ionic liquids were synthesized by an exothermic neutralization process between N-phenyl-N-ethanolamine and stoichiometric quantity of different acids, namely, propionic acid, butyric acid, pentanoic acid and hexanoic acid. After characterization by 1H NMR and 13C NMR spectroscopic methods, density (ρ), speed of sound (u), viscosity (η) and conductivity (σ) of neat ionic liquids have been measured 293.15 to 343.15 K and the refractive index (nD) was measured only at 303.15 K. The density and refractive index data were correlated by Gardas-Coutinho model and Lorentz-Lorenz mathematical equation, respectively, whereas viscosity and electrical conductivity were estimated by Vogel-Tammann-Fulcher (VTF) equation. Further experimental data used to calculate several derived thermodynamic properties such as thermal expansion coefficient (α), isentropic compressibility (βS), molar volume (Vm), standard entropy (S°), intermolecular free length (Lf), molar refraction (Rm) and free volume (fV). The decomposition temperature (Td) of synthesized ILs was investigated using TGA analysis. Finally, Conductor-like Screening Model for Real Solvents (COSMO-RS) computational method was also studied to understand the structural variations of the ionic liquids. © 2017 Elsevier B.V.